Impact of physical activity on the development of dementia - Pudło, Kornelia; Ochyra, Karolina; Bukała, Martyna; Frydrych, Jowita; Prucnal, Gabriela; Ryba, Karolina; Znamirowska, Katarzyna; Zacher, Klaudia; Rakoczy, Anna; Walkiewicz, Patrycja (Quality in Sport, 2025)
Issues related to disease prevention are being increasingly addressed, particularly through the prevention of diseases by identification and verification of risk factors. One condition that is associated with an increasing incidence among the aging population is dementia, which places a burden on health care systems and the caregivers. The purpose of this study is to explore the relationship between physical activity and the development of dementia based on the available literature. Understanding how exercise and sports can help prevent dementia may prove crucial in its prevention. Research indicates that physical activity has an impact on preventing and delaying the development of dementia by reducing cardiovascular risk factors and having a neuroprotective effect. However, the effectiveness of physical activity, the type of sport and environmental conditions plays a major role in this aspect. Notably, evidence suggests that contact sports and strenuous physical work can promote the development of dementia.